Effectiveness of a Social Media–Based Electronic Cigarette Prevention Program among Vocational Education Students in Surat Thani Province, Thailand: A Quasi-Experimental Study - Sudarat Damchuea; Thinyada Laenphet; Kanokwan Khamnan; Nipaporn Nobnorb; Isaree Padphai (YCAB Publisher, 2026)
Background: E-cigarette use among vocational students has increased in Thailand, highlighting the need for effective prevention strategies. This study developed a social media–based e-cigarette prevention program grounded in Social Support Theory to promote knowledge and self-protective behaviors among vocational education students in Surat Thani Province. Objective: To evaluate the effectiveness of a social media–based e-cigarette prevention program among vocational students between experimental and control groups. Methods: A quasi-experimental study was conducted among vocational education students in Surat Thani Province using multi-stage sampling. Participants were assigned at the institutional level to either an experimental group (n = 44), which received a 12-week social media–based prevention program, or a control group (n = 44), which continued usual institutional activities. Data were collected using validated questionnaires assessing knowledge, attitudes, perceived social support, and self-protective behaviors related to e-cigarette use. Independent t-tests and paired t-tests were used to analyze differences between and within groups. Results: After the intervention, the experimental group demonstrated significantly higher knowledge scores than the control group (Mean difference = 3.64, p < 0.001) and significantly greater self-protective behaviors (Mean difference = 1.31, p < 0.001). No statistically significant changes were observed in attitudes or perceived social support in either group. Conclusion: The social media–based prevention program was effective in improving knowledge and self-protective behaviors related to e-cigarette use among vocational students. However, attitudes and perceived social support did not significantly change. These findings suggest that social media may serve as a complementary tool for prevention-related educational efforts among vocational students.